Dragon Fruit â€“ A potentially healthy niche fruit crop in waiting - Karunakaran, G; Sriram, S; Arivalagan, M (Indian Horticulture, 2020)
Dragon Fruit (Hylocereus sp.) is a perennial, wide known as red Pitaya, has recently drawn much attention of South Indian growers, not only because of its attractive red or pink colour, loaded with functional food supplements and economic value as fruit, but also for rich antioxidant activity, vitamin C, fibres content. Therefore, Dragon Fruit can be called as a â€œhealthy fruitâ€. Studies conducted elsewhere indicates that its consumption strengthens the human immune system and could be used in the management of diabetes. Fruits can also be processed into juice, ice cream or wine.